Networking B2B Relationships and SMEs Internationalization in Search of Competitiveness - Elena-Mădălina VĂTĂMĂNESCU; Vlad-Andrei ALEXANDRU; Mădălina-Elena STRATONE; Elena Adriana BIEA (Communications of International Proceedings, 2023)
The paper seeks to examine different facets of business-to-business (B2B) relationships availed by small and medium-sized enterprises (SMEs) in international contexts. The theoretical approach is meant as a preamble for further conceptual and empirical endeavors, putting forward a context-driven perspective. The literature-based overview allows bringing up some important issues while discussing good managerial connections (especially those that take place between international partners). To begin, managers must always view interactions as mutually beneficial, which necessitates assuming the goals, potential, and expectations of all parties participating in the exchange. Second, managers must admit the cultural variation in the effects and possibilities for updating a given set of variables describing a set of relationships. Finally, at any given period in every connection, long or short, the fundamental qualities of the interaction up to that point may be tracked. The relationship's past reveals its essential essence and also establishes the groundwork for its potential development in the future. Prescription of the indefinite business relationship requires a thorough familiarity with the interaction's background.
Keywords: business-to-business (B2B) relationship marketing; small and medium-sized enterprises (SMEs); internationalization; competitiveness.